Differential PROTAC substrate specificity dictated by orientation of recruited E3 ligase - Blake E. Smith (Nature Portfolio, 2019)
PROTACs enable targeted protein degradation by recruiting an E3 ligase to a specific substrate but the determinants of selectivity are not fully understood. Here, the authors show that varying the linker between warhead and E3 ligand and the orientation of the E3 ligase allow tuning PROTAC selectivity toward different p38 isoforms.